Attitude and behaviour of society towards transport carbon emission pollution in Sintok, Kedah - Usman, Nora Fitriani; Rahim, Fatin; Mustaffa, Abaidullah (Universiti Utara Malaysia, 2019)
Carbon emission pollution and its effect on society have attracted international attention due to environmental, social and economic problems. However, it appears that society’s attitude and behaviour is still unclear about the effects of carbon emission from transport as an atmospheric pollutant. The purpose of this research is to study society’s behaviour using the Tripartite Model of Attitude (TMA) as the underpinning theory towards transportation with low carbon emission in Sintok. Kedah. The quantitative approach has been used by using self-administered survey questionnaires adopting a 5-point Likert scale with validated multi-item scale measurements. Quota sampling technique was used to sample 192 respondents from society in Sintok, Kedah. The dependent variable is behaviour with a single dimension. The independent variables are three components of attitude, namely cognition, affection and conation. Multiple regression has been used for data analysis and hypotheses testing. This research explored the behaviour of society using attitude sub-dimensions towards transportation with low carbon emission in Sintok, the state of Kedah, Malaysia. The main finding is that cognitive a sub-dimension of attitude is not supported. However, adequate and conative are supported.